Literasi Hukum : Typologi Kejahatan Investasi dan Manajemen Investasi Efektif - Syah Awaluddin; Mar’atun Shalihah; Evy Savitri Gani; Nadif Hidayat Pattimura; Ilham Ohoirenan (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2022)
Improving legal literacy in society has become an urgent need to prevent the increasing number of investment fraud cases. The lack of public understanding regarding the typology of investment crimes and effective investment management is often exploited by criminals to carry out fraudulent practices. This community service activity aims to provide education on legal literacy, particularly concerning the typology of investment crimes and safe investment management strategies. The methods used include legal socialization, case studies, and investment management training. The results of the activity showed active community participation in understanding the characteristics of illegal investments, such as Ponzi schemes and fraudulent investments, as well as grasping the principles of effective investment. Previously vulnerable to investment scams, the community is now more critical and aligned in selecting investment instruments. This activity is expected to contribute to building a legally aware society, capable of managing finances wisely and protected from the risks of investment crimes.